2007
DOI: 10.1007/s11104-007-9449-4
|View full text |Cite
|
Sign up to set email alerts
|

Mobilization of Cu and Zn by root exudates of dicotyledonous plants in resin-buffered solutions and in soil

Abstract: It has been frequently suggested that root exudates play a role in trace metal mobilization and uptake by plants, but there is little in vivo evidence. We studied root exudation of dicotyledonous plants in relation to mobilization and uptake of Cu and Zn in nutrient solutions and in a calcareous soil at varying Cu and Zn supply. Spinach (Spinacia oleracea L.) and tomato (Lycopersicon esculentum L.) were grown on resin-buffered nutrient solutions at varying free ion activities of Cu (pCu 13.0-10.4) and Zn (pZn … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(30 citation statements)
references
References 33 publications
2
28
0
Order By: Relevance
“…arsenate) for binding sites (Jones et al 2004;Fitz and Wenzel 2002;Wenzel et al 2003a). The mobilising effect of root exudates has been demonstrated in vitro (Mench and Martin 1991) and recently in resin buffered nutrient solutions and soil experiments (Degryse et al 2007;Shenker et al 2001). However, increased mobility was not necessarily associated with increased uptake in plants (Shenker et al 2001).…”
Section: Rhizosphere Controls Of Pollutant Bioavailability During Phymentioning
confidence: 95%
“…arsenate) for binding sites (Jones et al 2004;Fitz and Wenzel 2002;Wenzel et al 2003a). The mobilising effect of root exudates has been demonstrated in vitro (Mench and Martin 1991) and recently in resin buffered nutrient solutions and soil experiments (Degryse et al 2007;Shenker et al 2001). However, increased mobility was not necessarily associated with increased uptake in plants (Shenker et al 2001).…”
Section: Rhizosphere Controls Of Pollutant Bioavailability During Phymentioning
confidence: 95%
“…Soil properties such as soil metal concentration, pH and soil components will control soil metal bioavailability (Kirkham 2006). Plants can decrease metal availability because of plant removal of metals from the soil and can also enhance metal availability by the production of root exudates (Degryse et al 2008). In the present study, metal ) in the contaminated soils after nine consecutive crops of S. plumbizincicola "Unplanted" and "Planted" denote soil without phytoextraction and with nine crops of phytoextraction respectively; S1, lightly polluted soil; S2 and S3 intermediate polluted soils; S4, highly polluted soil.…”
Section: Plant Metal Uptake During Repeated Phytoextractionmentioning
confidence: 99%
“…There are two possible explanations. Firstly, the rhizosphere activity of the hyperaccumulator may increase metal availability by root exudates (Degryse et al 2008;). In the case of low metal concentrations in the soil solution and relative large metal potential pool size C and D) in different size soil fractions before and after repeated phytoextraction.…”
Section: Plant Metal Uptake During Repeated Phytoextractionmentioning
confidence: 99%
See 1 more Smart Citation
“…Neither of these studies, however, proved Zn mobilization from soil by citrate. Degryse et al (2008) showed that carboxylates exuded from roots of spinach (Spinacia oleracea L.) and tomato (Solanum lycopersicum L.) were able to mobilize Cu and Zn from a calcareous soil. On the other hand Gao et al (2009) showed that malate concentrations observed in the rhizosphere of rice had a negligible effect on the concentration of Zn in soil solution of a low Zn soil.…”
Section: Introductionmentioning
confidence: 99%